Analisis Tingkat Usabilitas Website Perguruan Tinggi Menggunakan System Usability Scale (SUS) - Anita Wulansari; Asif Faroqi; Tri Lathif Mardi Suryanto (Jurnal Teknologi Informasi dan Terapan, 2023)
In the digital era, the existence of a website is a necessity for universities. Websites can be an effective marketing tool because they can reach higher education audiences globally without being limited by geographic boundaries. However, website managers must ensure that the website has good quality and visibility. One tool for measuring the level of website usability was the System Usability Scale (SUS). SUS was chosen because it was considered a simple instrument but can provide an overview of the level of website usability. This research involved 866 student website users. The measurement results show that the website obtained an SUS score of 61.4. This score was then interpreted into three scales, namely Grade Scales, Adjective Ratings and Acceptability Ranges. The results show that the score were categorized into the "D", "Good" and "Marginal Low" categories for the Grade Scales, Adjective Ratings and Acceptability Ranges respectively. This SUS score shows a fairly low level of usability, therefore website improvements, especially in terms of website visuals, are important to do immediately.